COMPARATIVE RESEARCHES OF FRACTURES OF HIGH-STRENGTH CAST IRON IN THE AS-CAST AND DEFORMED STATE - A. I. Pokrovsky; I. N. Khrol (Литьë и металлургия)
The results of comparative studies of fracture surfaces of high-strength cast iron in the as-cast state and after hot direct extrusion through an aperture of a conical die are presented.The shape change of graphite inclusions and components of the metal matrix is examined with increasing the reduction ratio from 0 (as-cast state) to 80%.For the fist time, using the electrochemical etching of the metal matrix of the cast iron, it is demonstrated experimentally that at plastic deformation the ductile flow of graphite inclusions occurs without fracturing of the latter. The surface morphology of a deformed graphite inclusion is revealed. It is shown that inside the inclusion the strain is distributed non-uniformly: the peripheral zones are deformed to a larger extent while the central part may retain its original radial structure.The fact that the most part of graphite inclusions on the fracture surface of the deformed cast iron appeared undamaged (very small amount of fractured inclusions was observed) testifies against the common opinion that graphite acts as a crack nucleation site. A hypothesis is put forward that the crack nucleates in the metal matrix, presumably at the pearlite/ferrite interface, and propagates from one graphite inclusion to another rounding but not damaging the latter.